2015
DOI: 10.1007/s10096-015-2409-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic pulmonary aspergillosis in patients with tuberculosis from Iran

Abstract: In patients with preexisting lung disease, especially a cavity, Aspergillus can infect the surface of the cavity, causing chronic cavitary pulmonary aspergillosis (CCPA), and may form an aspergilloma, collectively called chronic pulmonary aspergillosis (CPA). In the present study, we assessed tuberculosis (TB) patients for CPA based on culture and serological methods. During a period of 1 year (from March 2013 to March 2014), we studied 124 patients with TB (94 with current TB and 30 with previous TB) at Masih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
55
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 36 publications
6
55
0
5
Order By: Relevance
“…Of note, five out of six azole-resistant isolates were recovered from CPA patients. The significant predilection to CPA is in agreement with the findings of recent studies in Iran which demonstrated that CPA is the most common clinical presentation of aspergillosis in individuals with healed tuberculosis (35). Importantly, patients with CPA require long-term maintenance antifungal therapy to improve symptoms and prevent the recurrence of infection (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…Of note, five out of six azole-resistant isolates were recovered from CPA patients. The significant predilection to CPA is in agreement with the findings of recent studies in Iran which demonstrated that CPA is the most common clinical presentation of aspergillosis in individuals with healed tuberculosis (35). Importantly, patients with CPA require long-term maintenance antifungal therapy to improve symptoms and prevent the recurrence of infection (36,37).…”
Section: Discussionsupporting
confidence: 89%
“…Symptoms include weight‐loss, severe fatigue, shortness of breath, and haemoptysis leading to a 5‐year case fatality rate of 20‐50% even when treated . Major risk factors are underling pulmonary diseases, especially those leading to a structural damage of the lung such as tuberculosis, non‐tuberculous mycobacteria (NTM) pulmonary diseases, chronic obstructive pulmonary disease (COPD) and other chronic pulmonary diseases . Despite common understanding CPA is not a disease of the severely immunocompromised host such as invasive aspergillosis, although the subacute invasive pulmonary aspergillosis (SAIA; formally called chronic necrotizing pulmonary aspergillosis), which is a sub‐entity of CPA, is usually seen in patients with a mild immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Major risk factors are underling pulmonary diseases, especially those leading to a structural damage of the lung such as tuberculosis, non-tuberculous mycobacteria (NTM) pulmonary diseases, chronic obstructive pulmonary disease (COPD) and other chronic pulmonary diseases. [10][11][12][13] Despite common understanding CPA is not a disease of the severely immunocompromised host such as invasive aspergillosis, although the subacute invasive pulmonary aspergillosis (SAIA; formally called chronic necrotizing pulmonary aspergillosis), which is a sub-entity of CPA, is usually seen in patients with a mild immunosuppression. All other forms of CPA including single aspergilloma, aspergillus nodule(s), chronic cavitary pulmonary aspergillosis (CCPA), and chronic fibrosing pulmonary aspergillosis (CFPA) are exclusively seen in patients with underlying respiratory disorders without severe immunosuppression.…”
Section: Introductionmentioning
confidence: 99%
“…In concordance with Kosmidis and Denning 11 who suggested that the persistence of lung cavities in TB patients with previous successful treatment increase the rate of aspergilloma, in our study all patients with fungus balls had a history of previous treated PTB in a period of 2‐16 years. In a recent study from Iran, the incidence rate of aspergilloma with CCPA and single aspergilloma were reported as 11.0% and 2.4%, respectively 12 . However, there are also some case report of aspergilloma in TB patients from Iran 13–15 …”
Section: Discussionmentioning
confidence: 99%
“…In several studies 9,12,16,18 , Aspergillus species especially A. fumigatus have been reported as the main aetiologic agent of culture‐proven cases of fungus balls. Therefore, the diagnostic approaches were often designed based on the diagnosis of aspergilloma.…”
Section: Discussionmentioning
confidence: 99%